2013
DOI: 10.3856/vol41-issue4-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data raise the possibility of cryptic species in the Brazilian endemic prawn Macrobrachium potiuna (Decapoda, Palaemonidae)

Abstract: ABSTRACT.A recent taxonomic revision indicated that Macrobrachium potiuna, an endemic prawn in Brazilian freshwater drainages, exhibits wide morphological variability along its limited geographical distribution. However, in some cases, taxonomic doubts at the species level have no clear morphological resolution. Considering that no molecular data of M. potiuna along its distribution were available to provide a complete and integrated overview, we analyzed 21 partial sequences (531 bp) from the mitochondrial 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
2
7
0
7
Order By: Relevance
“…; Carvalho et al . , ; Rossi & Mantelatto ). We therefore discount this relationship, which is ostensibly based on a misidentification in Kou et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Carvalho et al . , ; Rossi & Mantelatto ). We therefore discount this relationship, which is ostensibly based on a misidentification in Kou et al .…”
Section: Discussionmentioning
confidence: 98%
“…), as previously suggested for other palaemonid species (Carvalho et al . ) and fish of the Amazonian region (Cooke et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The genes concatenated analysis improve the diversity of evolutionary time, consequently revealed a more consistent phylogeny compared to previous morphological and molecular phylogenetics studies (Pereira 1997, Murphy and Austin 2005, Pileggi and Mantelatto 2010). The inclusion of the member of genus Cryphiops within Macrobrachium species was maintained in the phylogeny, and raises the question whether Macrobrachium is a monophyletic group (Pereira 1997, Murphy and Austin 2005, Pileggi and Mantelatto 2010, Carvalho et al 2013, Rossi and Mantelatto 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The molecular analysis was based on partial fragments of the 16S rDNA, 18S nDNA and COI mtDNA genes, which have been effective in solving different levels of relationships among decapod species (Schubart et al 2000, 2001a, b, Porter et al 2005, Pileggi and Mantelatto 2010, Mantelatto et al 2011, Vergamini et al 2011, Carvalho et al 2013, Rossi and Mantelatto 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Studies with fishes reported a similar pattern, providing evidence for the effect of divergent natural selection associated with the difference in water colour between the Negro River and Solimões-Amazon River (Cooke et al 2012a,b). Genetic divergence between hydrologically different, but interconnected, environments has been reported for other palaemonid species without a conspicuous and consistent morphological differentiation (Carvalho et al 2013). However, the characters described above allow the morphological distinction between Palaemon ivonicus and Palaemon yuna sp.…”
Section: Discussionmentioning
confidence: 73%